Analysis of Economic Independence of Micro, Small, and Medium Enterprises (MSMEs) in the Car Free Day Activity at the Stabat City Tribun Field - Santi Nurhasana Batubara; Fauzi Kurniawan (Economic: Journal Economic and Business, 2025)
This study aims to analyze the level of economic independence of Micro, Small, and Medium Enterprises (MSMEs) participating in the Car Free Day (CFD) activity at the Stabat City Tribune Field. The study used a qualitative descriptive approach with three main informants selected through purposive sampling. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using an interactive analysis model through the stages of data reduction, presentation, and drawing conclusions. The results of the study indicate that CFD activities play an important role in increasing the economic independence of MSMEs, as reflected in five main indicators: (1) free from consumer debt because all business capital comes from personal funds; (2) having strong confidence in business and self-confidence in facing challenges; (3) having investments in the form of savings, gold purchases, and social contributions; (4) being able to manage cash flow by separating personal and business finances and recording transactions regularly; and (5) having a positive mental attitude towards financial disruptions by being prepared to face risks and maintaining business stability. These findings confirm that CFD activities are not only a space for social interaction and marketing, but also function as an economic empowerment ecosystem that strengthens the financial independence and resilience of MSMEs in a sustainable manner.